PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) DENGAN DOUBLE LOOP PROBLEM SOLVING (DLPS) UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI PERBANDINGAN KELAS VII MTs NEGERI 4 KOTA PALU: Aplication of Problem Based Learning (PBL) Learning Model With Double Loop Problem Solving (DLPS) to Improve Student Learning Outcomes on Comparison Material For Class VII Students of MTs Negeri 4 Palu City - Kusumawati, Tuti Alawia; Rizal, Muh.; Hasbi, Muh.; Nasir, Rahma (Aksioma, 2024)
This study aims to describe the application of the Problem Based Learning (PBL) learning model with Double Loop Problem Solving (DLPS) to improve student learning outcomes in class VII comparison material at MTs Negeri 4 Palu City. The subjects in this study were VII C class students totaling 20 people. This type of research is Classroom Action Research (PTK) which refers to the research design of Kemmis and Mc. Taggart's research design, namely planning, action implementation, observation, and reflection. The results of this study indicate an increase in student learning outcomes from cycle I to cycle II marked by the increase in students whose scores reached the minimum completeness criteria as a whole. In cycle I, the number of students who were complete was 8 students with a percentage of completeness of 42.10% and in cycle II, the number of students who were complete was 11 students with a percentage of completeness of 73.33%. The results of observations of teacher and student activities in cycle I were in the good category and in cycle II were in the very good category. Based on the results of the study, it can be concluded that the application of the Problem Based Learning (PBL) learning model with Double Loop Problem Solving (DLPS) can improve student learning outcomes by using phases, namely (1) Orienting students to the problem, (2) Organizing students to learn, (3) Guiding individual and group investigations, (4) Developing and presenting work, and (5) Analyzing and evaluating the problem solving process